A conceptual study on the determinants of food donors to donate in surplus food redistribution - Hamik, Saidatul Akma; Mohamed, Ahmad Fariz; Sato, Mizuho (Faculty of Administrative Science and Policy Studies, 2023)
The phenomenon of food waste has expressed concern from both national and international authorities while community are hungry. Addressing these issues, most of developed countries focused on surplus food redistribution to protect the environment and help the needy. While the existing literature acknowledged the food donors, the research on the supply chain of surplus food redistribution among food donors is limited. This study investigates the determinants of food donors participate in food donation activities and developed a framework as a guideline for future empirical research.